THE DEVELOPMENT OF LEANING ACHIEVEMENT, CRITICAL THINKING, AND WORKING GROUP BEHAVIOR IN DUTIES OF CITIZENS SUBJECT USING THE 7E LEARNING CYCLE MODEL COMBINATION WITH GAME EDUCATION OF MATHAYOMSUKSA 6 STUDENTS - Tumthong, Damrong; Kraipetch, Chanita (Academic Journal of Thailand National Sports University, 2024)
Purposes: To compare academic achievement, critical thinking skills, and group work behavior after implementing the 7E learning cycle model in combination with educational games with 70% developmental criteria. Research method: a post-experimental measurement in one group, the sample is 24 students in Mathayomsuksa 6, Room 1, Demonstration School, Phetchaburi Rajabhat University, obtained by cluster random sampling. Research instruments: 1) 15 lesson plans totaling 36 hours; 2) learning achievement tests; 3) critical thinking skills assessment; and 4) group work behavior assessment. The data were analyzed using the mean, standard deviation, and one sample t-test. Results: The comparison of academic achievement in Civics Subjects, critical thinking skills, and group work behavior after implementation were significantly higher than the 70% development criteria at the level of .05. Conclusion: The 7E learning cycle model, combined with educational games after implementation, can develop civics subject's academic achievement, critical thinking skills, and group work behavior.